Legal Considerations Judex Factie Acquittal and Guilty Judgments by Judex Juris - Abdaud, Faisal; Umar, Wahyudi; Rustan, Ahmad; Ming-Hsi, Sung (Universitas Muhammadiyah Yogyakarta, 2024)
The corruption case involving the former North Konawe regent, Aswad Sulaiman, was acquitted by the Kendari Corruption Court in 2017, according to decision Number 56/Pid.Sus-TPK/2016/PN.Kdi. While the Supreme Court Cassation decision number 1964 K/PID.SUS/2017 decided that Defendant Aswad Sulaiman was proven legally and convincingly guilty of committing a crime by jointly committing an ongoing criminal act of corruption, imposing a prison sentence of 6 years and an IDR 200 million fine. If not paid, it will be replaced with imprisonment for 6 months, punished for producing a compensation of IDR 3,310,639,545 (three billion three hundred ten million six hundred thirty-nine thousand five hundred and forty-five rupiah). This study focuses on the legal ratio of the panel of judges in imposing an acquittal in the corruption case Number 56/Pid.Sus-TPK/2016/PN.Kdi and decision number 1964 K/PID.SUS/2017. This study used normative legal research with a statutory approach and a case approach, Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, which was last amended by Law Number 20 of 2001. The results are that the recovery of state financial losses must be investigated as the starting point that the defendant has committed corruption by not releasing him from criminal responsibility but only as a basis for mitigating considerations for the defendant. The judges deciding this case have at least gone through 3 stages: constating, qualifying, and constituting.